KAJIAN EROSI DAN NERACA HARA DALAM RANGKA REHABILITASI HUTAN DAN LAHAN (Kasus Di DAS Olonjonge,Parigi Moutong Sulawesi Tengah) - , Ir. Herman Harijanto, MP. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study was conducted in the area of Olonjonge watershed in order to: (i) examine the erosion rate in several area units existing in the area of Olonjonge watershed